أبعاد الشخصية البطلة في "مسرحية أبو الطيب المتنبي" ووقعها في تصوير شخص الشاعر: مقاربة سيميائية - زيتوني، كريمة (جامعة حسيبة بن بو علي الشلف - مخبر تعليمية اللغات وتحليل الخطاب, 2023)
تكمن قيمة هذا البحث في الوقوف على أهم شخصية شعرية قديمة، وهو أبو الطيب المتنبي، الذي أسال حبر الكثير من النقاد والدارسين على مر العصور، وهو نابغة زمانه في شعر الحكمة، وذلك بما جادت به قريحته الأدبية في نظم قصائد عمرت طويلا، ولازال صداها ووقعها بما تحمله من معان وأسلوب حداثي ممتدا إلى يومنا هذا. وبالتالي فالشاعر علامة فكرية ولغوية وشعرية وأيقونة سينمائية سجلت حضورها تمثيلا وشعرا حتى في الأداء المسرحي على غرار كتب التاريخ في الأدب العربي، إذ قام بعض الفنانين بتقديم عرض مسرحي يجسد فيه شخصية المتنتي وبيئته وشعره في: "مسرحية أبو الطيب المتنبي." ومن أهم النتائج التي توصلنا إليها هو أن العلامة المرئية قد تحقق وقعا أكثر في نفس المتلقي من جهة، ومن جهة أخرى استفادة الفنون من بعضها البعض لعله راجع إلى الطرح السيميائي في انتقال السمة من صيغتها اللغوية إلى صيغتها المرئية أو المسموعة (غير لفظية)، كما أن رقمنة العمل الأدبي بطريقة الفيديوهات أو التصوير المسرحي وحتى السينمائي من شأنه خلق فارق كبير في حفظ الأدب والأديب خاصة ومختلف الأعمال عامة. The value of this research lies in standing on the most important ancient poetic figure, and he is Abu al-Tayyib al-Mutanabbi, who has drawn the ink of many critics and scholars throughout the ages, and he is a genius of his time in the poetry of wisdom, and that is what his literary instinct demonstrated in the composition of poems that lived for a long time, and their resonance and impact still remains. With its meanings and modernist style extended to this day. Thus, the poet is an intellectual, linguistic, and poetic sign, and a cinematic icon whose presence was recorded in acting and poetry, even in theatrical performances similar to the history books in Arabic literature. One of the most important results that we reached is that the visual sign may achieve a greater impact on the recipient’s soul on the one hand, and on the other hand, the arts benefit from each other, perhaps due to the semiotic subtraction in the transition of the trait from its linguistic form to its visual or audible form (non-verbal), as well as The digitization of literary work through the method of videos or theatrical and even cinematography would create a big difference in preserving literature and writers in particular, and various works in general.
Keywords: المتنبي، أحمد بن الحسين، ت. 354 هـ. -- المسرح العربي -- العروض المسرحية -- الشخصيات البطلة